2009
DOI: 10.2174/156800909788166592
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Genes Involved in the Inverse Resistance Relationship Between Cisplatin and Paclitaxel Chemotherapy: Role of BRCA1

Abstract: A systematic review of cell models of acquired drug resistance not involving genetic manipulation showed that 80% of cell models had an inverse resistance relationship between cisplatin and paclitaxel [1] . Here we systematically review genetically modified cell lines in which the inverse cisplatin/paclitaxel resistance phenotype has resulted. This will form a short list of genes which may play a role in the mechanism of the inverse resistance relationship as well as potential markers for monitoring the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
2
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 80 publications
1
36
2
2
Order By: Relevance
“…This is usually greater than the increase in resistance seen per round from single-agent taxol treatments. This is the opposite of what we would have predicted given the inverse resistance relationship between platinum and taxanes (Stordal et al 2009). We hypothesised that pre-treatment with one agent would sensitise to the other.…”
Section: Resistance Developmentcontrasting
confidence: 82%
See 1 more Smart Citation
“…This is usually greater than the increase in resistance seen per round from single-agent taxol treatments. This is the opposite of what we would have predicted given the inverse resistance relationship between platinum and taxanes (Stordal et al 2009). We hypothesised that pre-treatment with one agent would sensitise to the other.…”
Section: Resistance Developmentcontrasting
confidence: 82%
“…A subsequent systematic review by (Stordal et al 2009), revealed that BRCA1 was the mostly likely genetic player in this relationship. Cells with BRCA1 defects have reduced efficiency in repairing DNA adducts and show increased apoptosis in response to platinums conferring sensitivity (Foulkes 2006;Xing et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It is also known that increased BRCA1 protein expression in prostate cancer is associated with significantly higher Gleason score, and more advanced stage 6 , as well as a poor outcome in thymic epithelial tumors 9 . A wealth of data from cell lines, mouse models and more recently from clinical studies have shown that BRCA1 can modulate response to chemotherapy [10][11][12][13] . BRCA1 mutations are not found in lung cancer, but decreased BRCA1 mRNA and protein expression due to promoter hypermethylation were found in 30% of NSCLC patients mostly in adenocarcinoma subtypes (P<0.014) (ref.…”
Section: Introductionmentioning
confidence: 99%
“…Because of this, the mechanism of resistance to anti-microtubule agents earn widespread concerns and many studies have reported on the subject. Several mechanisms explain the resistance, including decrease of the cellular accumulation mediated by P-glycoprotein (26) exportation and altered expression or post-translational modification of tubulin or other microtubule regulatory proteins (27). Recently, some studies have reported on the relationship a n d m e c h a n i s m b e t w e e n B R C A 1 e x p r e s s i o n a n d chemotherapy outcomes for carcinoma, but the results were controversial.…”
Section: Discussionmentioning
confidence: 99%